1974
DOI: 10.7567/jjaps.2s1.669
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Nickel Silicide NiSi2on Silicon

Abstract: The formation of structures of nickel silicides on Si have been studied by the use of glancing angle X-ray diffraction, MeV4He+ backscattering, reflection electron diffraction and replica electron microscopy. By reacting evaporated Ni films with Si wafers in the temperature range of 200 to 800°C, we have found three Ni silicides. The phase Ni2Si starts to form at 200°C at the Si-Ni interface. Around 350°C, the phase NiSi grows from the Si-Ni2Si interface. The NiSi is stable in the temperature range of 350 to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(25 citation statements)
references
References 0 publications
2
22
1
Order By: Relevance
“…However, nickel di-silicide (NiSi 2 ) formed from the low resistivity phase NiSi has the lowest lattice mismatch to Si and shows good epitaxial growth on Si [20,23]. NiSi 2 exhibits good thermal stability up to high temperatures of about 1000 • C. NiSi 2 loses adhesion to Si near its melting point of ∼993 • C [21], thereafter it starts to agglomerate with grain boundary grooving, followed by grain separation and formation of silicide islands, resulting in a dramatic increase in sheet resistance [20,[24][25][26][27]. This thermal instability is the main drawback which restricts its applications in deep submicron devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nickel di-silicide (NiSi 2 ) formed from the low resistivity phase NiSi has the lowest lattice mismatch to Si and shows good epitaxial growth on Si [20,23]. NiSi 2 exhibits good thermal stability up to high temperatures of about 1000 • C. NiSi 2 loses adhesion to Si near its melting point of ∼993 • C [21], thereafter it starts to agglomerate with grain boundary grooving, followed by grain separation and formation of silicide islands, resulting in a dramatic increase in sheet resistance [20,[24][25][26][27]. This thermal instability is the main drawback which restricts its applications in deep submicron devices.…”
Section: Introductionmentioning
confidence: 99%
“…NiSi has been also reported to agglomerate during the silicidation process at temperature as low as 600 • C [6][7][8][9][10][11][12]. This thermal instability of NiSi is a drawback in applying it to CMOS manufacturing and integration process [3,12,[20][21][22]. However, nickel di-silicide (NiSi 2 ) formed from the low resistivity phase NiSi has the lowest lattice mismatch to Si and shows good epitaxial growth on Si [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…When a metal/Si interface is subject to annealing, silicidation occurs. For the Ni/Si interface, silicidation takes place at temperatures as low as 200°C and various phases of Ni silicide are formed depending on the annealing temperature (12). When the silicidation experiment is performed between Ni and Sepassivated Si(100), we have found that silicidation is suppressed up to an annealing temperature of 500°C (13).…”
Section: Monolayer Passivationmentioning
confidence: 96%
“…The formation of Ni 2 Si and its transformation into NiSi rely on the diffusioncontrolled phenomena, 9 whereas the formation of NiSi 2 is initiated by a nucleation-controlled process. 2,10 The temperature of the Ni silicide formation between a thin Ni film and a film of amorphous silicon is noticeably lower than that of the silicide grown at the Ni-crystalline Si interface. For example, the reaction between NiSi films and a-Si was reported to lead to diffusion-controlled growth of NiSi 2 at 400°C.…”
Section: Introductionmentioning
confidence: 97%